Juvenile Myoclonic Epilepsy. Update - I. V. Volkov (Эпилепсия и пароксизмальные состояния, 2020)
Juvenile myoclonic epilepsy (JME) is a common disease. However, some aspects of etiology and pathogenesis are not yet fully clarified. This publication describes the development of ideas about JME, the types of seizures that occur in JME, provides a list of triggering factors and a prognosis severity scale that depending on these triggering factors. The section on JME diagnostics discusses methods of neuroimaging, electroencephalography, and approaches to assessing the mental status of JME patients. The data of meta-analysis of prevalence and risk factors of refractory JME in the context of assessment of the disease state and prognosis are presented. The data on advantages and disadvantages of various Antiepileptic Drugs (AEDs) for the control of the disease are considered. The results of the own study of AED spectrum and effectiveness in gender-sensitive and ILAE-recommended therapy in adults, as well as the GENERAL study of perampanel efficacy and safety in patients with idiopathic generalized epilepsy, are presented. It confirmed the high efficacy of the perampanel primarily for  myoclonic seizures and generalized tonic-clonic seizures. A case study of a female patient with JME was also described, in which refractory to therapy was noted, including due to low compliance to the prescribed therapy.